DEVELOPMENT OF A NEW ONE-EYE IMPLANT BY 3D BIOPRINTING TECHNIQUE (REVUE ROUMAINE DES SCIENCES TECHNIQUES — SÉRIE ÉLECTROTECHNIQUE ET ÉNERGÉTIQUE, 2023)
The paper analyzes the possibility of implementing a new eye implant using the 3D bioprinting technique and the experimental model underlying it. The paper includes the stages of image processing using Digital Imaging and Communications in Medicine (DICOM) and the processing of the eye implant, results, and exploitation. In the exploitation part of the eye implant, the aims are optimizing the image processing stages and refining the precision of the calibration model. In the manufacturing part, the new eye implant is fabricated with the help of machines. These machines are suitable for manufacturing structures with their porosity controlled by additive manufacturing techniques. The feasibility of using 3D printing techniques using biocompatible materials in structures with predetermined porosity was demonstrated to manufacture a customized eye implant using medical imaging Computed Tomography (CT) results. The work was performed within the OrbImplant Project.
Keywords: Eye implant; Digital imaging and communications in medicine (DICOM); Implant mounting